Crop Growth and Seed Quality of BRRI dhan28 Rice as Influenced by Nitrogen Rates (South Asian Journal of Agriculture, 2025)
Nitrogen as a major plant nutrient element limits rice production to a great extent. The current inquiry was done to verify the role of various nitrogen levels on growth of crop and seed quality of Boro rice cv. BRRI dhan28.The research was directed in a Randomized Complete Block Design (RCBD) and imitated quadruple. The treatments consist of six nitrogen doses, N0= 0, N1 = 35, N2 = 70, N3 = 105, N4 = 140, and N5 = 175 kg N ha-1as urea. Data on crop growth as well as seed quality characters were assembled and scrutinized statistically. Results disclosed that CGR and RGR were the maximum at 45-60 DAT when a dose of 175 kg ha-1 was maintained. The seed quality parameters were greatly influenced by various nitrogen treatments except germination (%) and the higher three nitrogen doses displayed significantly superior performances compared to the lower three nitrogen levels. Conversely, nitrogen application reveals linear but weak linkage with seed quality attributes. It could be concluded that application of nitrogen @ 105 kg ha-1or higher dose is proper for better crop progression and production of premium class seeds from BRRI dhan28.South Asian J. Agric., Vol. 10, No.1-2, 2024: 54-61